(untitled) (International Journal of Engineering and Computer Science, 2018)
Event-driven wireless sensor networks have been identified as one of the key areas in the field of wireless communication, where most of the time the network will be in light traffic load situation. When an event has detected, large number of packets will be generated. A MAC protocol designed for this kind of WSNs should be able to swiftly adapt to both light and heavy traffic load situations of the network. Here, implemented a receiver-centric MAC protocol called RC-MAC that integrates duty cycling and receiver centric scheduling. To handle heavy traffic load situation triggered by an event, RC-MAC takes advantage of tree based topology and multichannel technique to assist medium access scheduling. Different parent children sets are assigned to different channels. During light traffic load situation, there will be idle listening of sender in existing RC-MAC protocol, when short beacon interval is used. It reduces energy efficiency of existing RC-MAC. Also, during heavy traffic load situation, packet scheduling is not used in existing RC-MAC. So, a randomization of beacon technique enabled RC-MAC is designed to provide energy efficiency in both short beacon interval and large beacon interval cases. Also, packet scheduling is introduced along with receiver-centric scheduling and hence provides better end to end delay compared to existing approach.